The seduction of craft: Making and value in artisanal labour - Makovicky, Nicolette (Journal of material culture, 2020)
Drawing on fieldwork amongst lacemakers in Slovakia, this article examines the relationship between practices of making and the production of value in artisanal labour. The author shows that the processes of making challenged artisans’ perceptions of the natural distribution of agency between humans and objects, resulting in feelings of ontological insecurity. Arguing that they perceived this insecurity as a problem of ethics, as well as a problem of agency, she demonstrates how the intellectual and sensual experience of manufacture was constitutive of the ways in which artisans perceived the value of their craftwork. Taking this approach, the article seeks to disrupt the anthropological habit of framing questions about value in terms of domestic economies, global markets and aesthetic regimes, and making in terms of skilled practice, embodied knowledge and knowledge transmission. The author also suggests that scholars ought to pay more attention to the ways in which ethical considerations are grounded in our ontological disposition towards the material world.